Connecting Beyond the Screen: Exploring Loneliness and the Preference for Having Virtual Friends in Urban Populations in Indonesia - Erica, Luisa (Universitas PGRI Yogyakarta, 2025)
Loneliness is a prevalent issue among urban populations, often leading to social withdrawal, or hikikomori, and leading to virtual friendships as alternative sources of connection. This study used a multiple-methods approach to explore the virtual friendship phenomenon in Indonesia, combining quantitative analysis of loneliness, hikikomori tendencies, and intentions to form virtual friendships, with qualitative insights into the characteristics of an ideal virtual friend. Data from 153 participants aged 25–35 showed significant correlations between all aspects of hikikomori (p<.001). A t-test revealed that individuals who had engaged in virtual friendships reported significantly higher loneliness (t = 9.2134, p < .001) measured using SELSA-S. Qualitative analysis showed that the most valued traits were being a good listener with unconditional acceptance. These findings highlight the need for public mental health initiatives, particularly in Indonesia, to address loneliness through digital and face-to-face interventions, in line with national efforts to strengthen community-based mental health support. Keywords: urban citizen, isolation, loneliness, virtual friend